Pesan Moral Perbudakan dalam Al-Qur'an Pesan Kemanusiaan yang Terlupakan - Agus Muhammad (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
Generally, the steps for liberating slaves in the Qur’an are conducted in three gradual phases. The first step is the announcement of the liberation of the slaves, where the liberation of the slaves is recommended and declared to be a virtue that has its reward in the hereafter. The second step is the implementation phase, where the liberation of the slaves becomes sanctioned by law. The third step is shutting off the roots of the slavery. At the time of the arrival of Islam, one of the sources of slavery was warfare. The moral message in the liberation of the slaves is Islam’s commitment to value the dignity of human beings as creatures of God.